Catalyst for hydrogen storage material as well as preparation method and application of catalyst

By loading transition metal nanoclusters on CeO2 nanorods, synergistic effects with MgH2 are formed, and the problems of high hydrogen release temperature and low hydrogen absorption/drain rate of MgH2 materials are solved, achieving low-cost and efficient hydrogen storage materials performance improvement , has the application potential of on-board hydrogen storage.

CN119158594AActive Publication Date: 2024-12-20GANJIANG INNOVATION ACAD CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411301939.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-20
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

The high hydrogen release temperature and low hydrogen absorption/drain rate of MgH2 materials limit their commercial development in hydrogen storage materials, making it difficult to meet the needs of hydrogen storage devices.

Method used

CeO2 nanorods are used as carriers to load transition metal nanoclusters, such as Ni, Pd or Co, to form a synergistic effect, reduce the hydrogen release temperature of MgH2 and improve its hydrogen absorption/discharge kinetics.

Benefits of technology

It significantly reduces the hydrogen discharge temperature of MgH2, improves its hydrogen absorption/discharge rate and circulation performance, and has low cost, and has the application potential of on-board hydrogen storage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119158594A_ABST
    Figure CN119158594A_ABST
Patent Text Reader

Abstract

The invention provides a catalyst for a hydrogen storage material as well as a preparation method and application of the catalyst. The catalyst for the hydrogen storage material comprises a CeO2 nanorod and a transition metal nanocluster loaded on the CeO2 nanorod, the transition metal nanocluster comprises any two of a Ni element, a Pd element, a Co element or a Mn element. According to the catalyst for the hydrogen storage material, the CeO2 nanorods and the transition metal nanoclusters can form strong metal-carrier interaction, and the hydrogen storage dynamic performance of the MgH2 material can be synergistically improved; meanwhile, the transition metal nanocluster with the two elements can effectively improve the hydrogen absorption / desorption performance of MgH2. Therefore, by compounding the catalyst with an MgH2 material, the hydrogen desorption temperature of MgH2 can be reduced, the hydrogen absorption / desorption dynamic performance of MgH2 can be improved, and the cycle performance can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogen storage, and relates to a catalyst for hydrogen storage material and a preparation method and application thereof. Background Art

[0002] Hydrogen energy is a very ideal energy source. In the entire hydrogen energy industry chain, due to the mismatch between hydrogen supply and demand, hydrogen storage and transportation have become the key to the large-scale industrial application of hydrogen. However, the storage and transportation of hydrogen energy is difficult, which has become a major bottleneck restricting the development of the hydrogen energy industry. Realizing low-cost, high-efficiency, high-safety and high-density reversible hydrogen storage has become the key to realizing the large-scale development of the hydrogen energy industry. The hydrogen storage technologies currently under research and development mainly include four methods: high-pressure gaseous hydrogen storage, solid-state hydrogen storage, organic liquid hydrogen storage and low-temperature liquid hydrogen storage. Among them, solid-state hydrogen storage technology has been used in mobile test instruments, fuel cells and other aspects to supply hydrogen because of its mild hydrogen absorption / desorption pressure, high safety properties, low leakage rate, and high volume hydrogen storage density. In addition, it is also used for efficient hydrogen pressurization such as hydrogen purification and hydrogen refueling stations, especially in some hydrogen fuel cell vehicles.

[0003] Among solid hydrogen storage materials, MgH2 has a mass hydrogen storage density of up to 7.6wt.%, which is much higher than the theoretical hydrogen storage density of several alloys. Therefore, it is more favored by researchers. The reaction enthalpy △H of MgH2 is about -75kJmol -1 MgH2 is an ionic hydride with a strong ionic bond, so a higher temperature (above 300°C) is required to break the Mg-H bond to release hydrogen. In addition, its hydrogen absorption / desorption rate is slow, which makes it difficult to meet the rate requirements of hydrogen storage devices, seriously restricting its commercial development in hydrogen storage materials.

[0004] Therefore, it is necessary to provide a solution that can reduce the dehydrogenation temperature of MgH2 material and increase its hydrogen absorption / dehydrogenation rate. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention aims to provide a catalyst for hydrogen storage materials and a preparation method and application thereof. The catalyst for hydrogen storage materials provided by the present invention comprises CeO2 nanorods and transition metal nanoclusters loaded on CeO2 nanorods, which, after being composited with MgH2 materials, can significantly reduce the dehydrogenation temperature of MgH2, improve the kinetic performance of hydrogen absorption / dehydrogenation of MgH2, and increase its hydrogen absorption / dehydrogenation rate.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a catalyst for a hydrogen storage material, the catalyst for a hydrogen storage material comprising CeO2 nanorods, and transition metal nanoclusters supported on the CeO2 nanorods;

[0008] The transition metal nanoclusters include any two of the elements Ni, Pd, Co or Mn.

[0009] The catalyst for hydrogen storage material provided by the present invention uses CeO2 nanorods as carriers, which have low cost and excellent catalytic performance, and have a large number of oxygen vacancies, which can form a strong metal-carrier interaction with transition metal nanoclusters, forming a synergistic effect to improve the kinetic performance of MgH2 materials; and the catalyst has a nanorod-like morphology, which can play a certain cutting role on MgH2 in the composite process with MgH2 materials, further reducing the particle size of MgH2, so that the catalyst and MgH2 have a larger contact area, thereby further improving the hydrogen storage kinetic performance of MgH2 materials; at the same time, the Ce element in the CeO2 nanorods is a rare earth metal element, which has rich energy levels and special 4f electron transition characteristics;

[0010] The transition metal nanoclusters include any two of Ni, Pd, Co or Mn, wherein Ni, Co and Mn are all 3d transition metal elements, so it can be known that the transition metal nanoclusters will contain at least one 3d transition metal element. The introduction of 3d transition metal elements can effectively improve the hydrogen absorption / desorption performance of MgH2, which is mainly related to the special electronic structure of 3d transition metals, and they can form hydrides with hydrogen, playing the role of "overflow" or "hydrogen pump" in the process of hydrogen absorption / desorption. Because the transition metal hydride is thermodynamically more unstable than pure Mg, it will first separate from the hydrogen atom in the process of hydrogen absorption / desorption, thereby playing the role of transmitting "hydrogen"; the Pb element exhibits a unique electronic configuration in the dehydrogenation process, which can improve the surface activity of the material, catalyze the breaking of the Mg-H bond, and reduce the dehydrogenation temperature of MgH2;

[0011] Under the synergistic effect of CeO2 nanorods and transition metal nanoclusters in the catalyst, the hydrogen absorption / desorption activity on the surface, grain boundary and phase boundary of the MgH2 material can be improved, providing nucleation cores, thereby reducing the nucleation energy barrier of MgH2 and the activation energy of the entire hydrogen absorption / desorption process; and the dissociation energy of hydrogen molecules on the magnesium surface can be reduced (the original dissociation energy is as high as 1.15eV); at the same time, the interaction between the unsaturated d / f electron layer of the metal in the catalyst and the valence electrons of H will weaken the Mg-H bond, thereby improving the hydrogen desorption performance of the MgH2 material;

[0012] In summary, by combining the catalyst of the present invention with MgH2 material, the dehydrogenation temperature of MgH2 can be greatly reduced, the hydrogen absorption / dehydrogenation kinetics of MgH2 can be improved, the hydrogen absorption / dehydrogenation rate can be increased, and the cycle performance can be improved. In addition, the composite hydrogen storage material has the characteristics of light weight and low cost, so that it has the application potential of on-board hydrogen storage.

[0013] Preferably, the length of the CeO2 nanorods is 50-80 nm, for example, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm or 80 nm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0014] Preferably, the diameter of the CeO2 nanorods is 7-8 nm, for example, 7 nm, 7.2 nm, 7.4 nm, 7.6 nm, 7.8 nm or 8 nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0015] Preferably, the transition metal nanoclusters include Ni and Pd elements.

[0016] In the present invention, under the synergistic effect of Ni element, Pd element and CeO2 nanorods in transition metal nanoclusters, a catalyst containing very little Pd element can achieve the effects of greatly reducing the dehydrogenation temperature of MgH2, improving the kinetic performance of hydrogen absorption / dehydrogenation of MgH2 and increasing the hydrogen absorption / dehydrogenation rate, and significantly reduce the amount of Pd precious metal element, which can significantly reduce the cost of the catalyst; at the same time, Ni element and Pd element can form Mg6Ni / Mg6Pd clusters in the process of hydrogen absorption / dehydrogenation, and jointly catalyze MgH2, so that the hydrogen storage material obtained by compounding the catalyst and the MgH2 material has a higher hydrogen storage capacity and a faster hydrogen absorption / dehydrogenation rate.

[0017] Preferably, the ratio of the total number of atoms of the Ni element and the Pd element to the number of atoms of the CeO2 nanorods is 0.05-0.3, for example, it can be 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29 or 0.30, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0018] The present invention uses a trace amount of Pd and Ni elements on CeO2 nanorods to greatly reduce the amount of precious metals used and reduce the catalyst cost. The catalyst cost of the present invention of the trace amount of Pd and Ni elements on CeO2 nanorods is much lower than the cost of the composite catalyst of the two elements of Pd and Ni.

[0019] Preferably, the molar ratio of the Ni element to the Pd element is (1-3):(1-3), wherein the selection range of the Ni element can be, for example, 1, 2 or 3, and the selection range of the Pd element can be, for example, 1, 2 or 3, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0020] Preferably, the transition metal nanoclusters include Co and Mn elements.

[0021] In the present invention, when the transition metal elements in the transition metal nanoclusters are composed of Co and Mn, it can also play the role of lowering the dehydrogenation temperature of MgH2, improving the kinetics of hydrogen absorption / dehydrogenation of MgH2 and increasing the hydrogen absorption / dehydrogenation rate. However, since the reversibility of hydrogen absorption / dehydrogenation formed by metals such as Co and Mn and Mg, such as Mg2Co and MnO2, is relatively poor, the hydrogen storage material obtained by combining the catalyst and the MgH2 material has a slightly lower hydrogen storage capacity, which is lower than the combination of Ni and Pd.

[0022] Preferably, the ratio of the total number of atoms of the Co element and the Mn element to the number of atoms of the CeO2 nanorods is 0.05-0.3, for example, it can be 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29 or 0.30, but is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable.

[0023] Preferably, the molar ratio of the Co element to the Mn element is (1-3):(1-3), wherein the selection range of the Co element can be, for example, 1, 2 or 3, and the selection range of the Mn element can be, for example, 1, 2 or 3, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] In a second aspect, the present invention provides a method for preparing the catalyst for hydrogen storage material according to the first aspect, the preparation method comprising:

[0025] (1) mixing CeO2 nanorods, a transition metal source and a solvent for loading to obtain a loaded product; wherein the transition metal source comprises any two of a Ni source, a Pd source, a Co source or a Mn source;

[0026] (2) The supported product is subjected to a heating reduction reaction to obtain the catalyst for the hydrogen storage material.

[0027] The present invention realizes loading transition metal nanoclusters on CeO2 nanorods through a deposition precipitation method and a thermal reduction method to obtain a catalyst for hydrogen storage materials.

[0028] Preferably, the method for preparing CeO2 nanorods in step (1) comprises:

[0029] (a) mixing a solution containing a Ce source and a solution containing a precipitant, and then performing a hydrothermal reaction to obtain a hydrothermal reaction product;

[0030] (b) calcining the hydrothermal reaction product to obtain the CeO2 nanorods.

[0031] The CeO2 nanorods prepared by the hydrothermal method in the present invention are more suitable as catalyst carriers.

[0032] Preferably, the Ce source includes a Ce salt.

[0033] Optionally, the Ce salt includes Ce(NO3)3·6H2O.

[0034] Preferably, the precipitant comprises an alkaline substance.

[0035] Optionally, the alkaline substance comprises NaOH.

[0036] Preferably, the temperature of the hydrothermal reaction is 90-110°C, for example, it can be 90°C, 95°C, 100°C, 105°C or 110°C; the time of the hydrothermal reaction is 22-26h, for example, it can be 22h, 23h, 24h, 25h or 26h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] Preferably, the calcination temperature is 380-420°C, for example, 380°C, 390°C, 400°C, 410°C or 420°C; the calcination time is 3-5h, for example, 3h, 4h or 5h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] Preferably, the transition metal source in step (1) comprises a Ni source and a Pd source.

[0039] Preferably, the Ni source includes NiCl2 and / or NiCl2·6H2O; the Pd source includes H2PdCl4 and / or PdCl2.

[0040] Preferably, the transition metal source in step (1) comprises a Co source and a Mn source.

[0041] Preferably, the Co source includes CoCl2 and / or Co(NO3)2·6H2O; and the Mn source includes MnCl2 and / or KMnO4.

[0042] Preferably, the mixing in step (1) specifically includes the following steps: first performing a first mixing, then adding a pH adjuster dropwise until the pH value of the system is 9-10 (for example, it can be 9, 9.1, 9.2, 9.3, 9.4, 9.5, 9.6, 9.7, 9.8, 9.9 or 10, etc.), and then performing a second mixing.

[0043] Optionally, the pH adjuster comprises sodium carbonate.

[0044] Preferably, the first mixing and the second mixing are both accompanied by stirring.

[0045] Preferably, the first mixing time is 20-40 min, for example, 20 min, 25 min, 30 min, 35 min or 40 min, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0046] Preferably, the second mixing time is 1-3 hours, for example, 1 hour, 2 hours or 3 hours, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0047] Preferably, the atmosphere of the heating reduction reaction in step (2) is a reducing atmosphere.

[0048] Preferably, the gas in the reducing atmosphere includes hydrogen and argon; the volume ratio of the hydrogen and the argon is (1-2):(8-9), for example, it can be 1:9 or 2:8, etc. Other unlisted values ​​within this numerical range are also applicable.

[0049] Preferably, the temperature of the heating reduction reaction is 380-420°C, for example, 380°C, 390°C, 400°C, 410°C or 420°C, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0050] Preferably, the heating reduction reaction time is 3-5 h, for example, 3 h, 4 h or 5 h, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0051] As a preferred technical solution of the present invention, the preparation method specifically comprises the following steps:

[0052] (I) dissolving Ce(NO3)3·6H2O in water to obtain a solution containing a Ce source, and dissolving NaOH in water to obtain a solution containing a precipitant; rapidly mixing the solution containing a Ce source and the solution containing a precipitant under stirring, and continuing to stir and mix at room temperature for 1-2 hours, and then performing a hydrothermal reaction at 90-110°C for 22-26 hours, and then washing and vacuum drying in sequence to obtain a hydrothermal reaction product; calcining the hydrothermal reaction product at 380-420°C for 3-5 hours to obtain CeO2 nanorods;

[0053] (II) dispersing the CeO2 nanorods, NiCl2 and H2PtCl4 in water, stirring and mixing at room temperature for 20-40 minutes, then adding a pH adjuster dropwise until the pH value of the system is 9-10, and then continuing to stir and mix for 1-3 hours to load, and then washing and vacuum drying in sequence to obtain a loaded product;

[0054] (III) In a reducing atmosphere of hydrogen and argon, the supported product is subjected to a heating reduction reaction at 380-420° C. for 3-5 hours to obtain the catalyst for hydrogen storage material.

[0055] In a third aspect, the present invention provides a hydrogen storage material, which is obtained by ball milling a MgH2 material and the hydrogen storage material described in the first aspect with a catalyst.

[0056] Preferably, based on the total mass of the hydrogen storage material, the mass fraction of the catalyst for the hydrogen storage material is 5-15%, for example, it can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0057] Preferably, the ball milling speed is 450-500 rpm, for example, it can be 450 rpm, 460 rpm, 480 rpm or 500 rpm; the ball milling time is 20-25 h, for example, it can be 20 h, 21 h, 22 h, 23 h, 24 h or 25 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0058] In the present invention, when the ball milling time is controlled to be 20-25 hours, the particle size of the hydrogen storage material can be made smaller, the uniformity of phase distribution can be improved, and thus the hydrogen absorption / desorption kinetics and cycle performance can be improved.

[0059] Exemplarily, the present invention provides a specific method for preparing a hydrogen storage material, comprising:

[0060] Under an inert atmosphere, MgH2 material, a catalyst for hydrogen storage material and stainless steel beads are placed in a ball milling jar and sealed, hydrogen is filled into the jar, and then ball milling is performed at a rotation speed of 450-500 for 20-25 hours to obtain a hydrogen storage material.

[0061] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0062] Compared with the prior art, the present invention has the following beneficial effects:

[0063] The catalyst for hydrogen storage material provided by the present invention uses CeO2 nanorods as carriers, which have low cost and excellent catalytic performance, and have a large number of oxygen vacancies, which can form a strong metal-carrier interaction with transition metal nanoclusters, forming a synergistic effect to improve the kinetic performance of MgH2 materials; and the catalyst has a nanorod-like morphology, which can play a certain cutting role on MgH2 in the composite process with MgH2 materials, further reducing the particle size of MgH2, so that the catalyst and MgH2 have a larger contact area, thereby further improving the hydrogen storage kinetic performance of MgH2 materials; at the same time, the Ce element in the CeO2 nanorods is a rare earth metal element, which has rich energy levels and special 4f electron transition characteristics;

[0064] The transition metal nanoclusters include any two of Ni, Pd, Co or Mn, wherein Ni, Co and Mn are all 3d transition metal elements, so it can be known that the transition metal nanoclusters will contain at least one 3d transition metal element. The introduction of 3d transition metal elements can effectively improve the hydrogen absorption / desorption performance of MgH2, which is mainly related to the special electronic structure of 3d transition metals, and they can form hydrides with hydrogen, playing the role of "overflow" or "hydrogen pump" in the process of hydrogen absorption / desorption. Because the transition metal hydride is thermodynamically more unstable than pure Mg, it will first separate from the hydrogen atom in the process of hydrogen absorption / desorption, thereby playing the role of transmitting "hydrogen"; the Pb element exhibits a unique electronic configuration in the dehydrogenation process, which can improve the surface activity of the material, catalyze the breaking of the Mg-H bond, and reduce the dehydrogenation temperature of MgH2;

[0065] Under the synergistic effect of CeO2 nanorods and transition metal nanoclusters in the catalyst, the hydrogen absorption / desorption activity on the surface, grain boundary and phase boundary of MgH2 material can be improved, providing nucleation cores, thereby reducing the nucleation energy barrier of MgH2 and the activation energy of the entire hydrogen absorption / desorption process; and the dissociation energy of hydrogen molecules on the magnesium surface can be reduced; at the same time, the interaction between the unsaturated d / f electron layer of the metal in the catalyst and the valence electrons of H will weaken the Mg-H bond, thereby improving the hydrogen desorption performance of the MgH2 material;

[0066] In summary, by combining the catalyst of the present invention with MgH2 material, the dehydrogenation temperature of MgH2 can be greatly reduced, the hydrogen absorption / dehydrogenation kinetics of MgH2 can be improved, the hydrogen absorption / dehydrogenation rate can be increased, and the cycle performance can be improved. In addition, the composite hydrogen storage material has the characteristics of light weight and low cost, so that it has the application potential of on-board hydrogen storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0067] Figure 1 This is a TEM image of the catalyst for hydrogen storage material provided in Example 3 of the present invention.

[0068] Figure 2 This is a SEM image of the hydrogen storage material provided in Example 3 of the present invention.

[0069] Figure 3 This is a dehydrogenation test curve of the hydrogen storage material provided in Example 3 of the present invention at different temperatures.

[0070] Figure 4 This is a hydrogen absorption test curve of the hydrogen storage material provided in Example 3 of the present invention at different temperatures.

[0071] Figure 5 This is a dehydrogenation test curve of the hydrogen storage material provided in Comparative Example 1 of the present invention at different temperatures.

[0072] Figure 6 This is a hydrogen absorption test curve of the hydrogen storage material provided in Comparative Example 1 of the present invention at different temperatures. DETAILED DESCRIPTION

[0073] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0074] Example 1

[0075] This embodiment provides a catalyst for hydrogen storage material, including CeO2 nanorods, and transition metal nanoclusters supported on the CeO2 nanorods;

[0076] The length of the CeO2 nanorods is 50-80nm and the diameter is 7-8nm; the transition metal elements in the transition metal nanoclusters are composed of Ni and Pd elements; the ratio of the total number of atoms of the Ni and Pd elements to the number of atoms of the CeO2 nanorods is 0.05, and the molar ratio of the Ni and Pd elements is 1:1; the catalyst for the hydrogen storage material is recorded as 0.05NiPd / CeO2.

[0077] This embodiment also provides a method for preparing the above-mentioned catalyst for hydrogen storage material, comprising the following steps:

[0078] (1) preparing the catalyst according to the composition of 0.05NiPd / CeO2;

[0079] (2) Ce(NO3)3·6H2O and NaOH were dispersed in deionized water to form two solutions, which were fully stirred and then quickly mixed. After continuous stirring for 1 hour, the sample was transferred to a reactor for hydrothermal reaction at 100°C for 24 hours. The material obtained after the hydrothermal reaction was washed with deionized water until neutral, and then washed again with anhydrous ethanol. After that, it was vacuum dried at 80°C for 12 hours, ground and passed through a 100-mesh molecular sieve. The sieved sample was transferred to a muffle furnace and calcined at 400°C for 4 hours to synthesize CeO2 nanorods.

[0080] (3) The synthesized CeO2 nanorod carrier was dispersed together with NiCl2 and H2PdCl4 in deionized water. After stirring at room temperature for 30 minutes, 1M Na2CO3 solution was added dropwise to adjust the pH value of the system to 9, and then the mixture was continuously stirred for 2 hours for loading. The obtained material was then washed with deionized water until neutral, washed again with anhydrous ethanol, and vacuum dried at 80°C for 12 hours. The dried sample was transferred to a tubular furnace and heated at 400°C for reduction reaction for 4 hours in a mixed atmosphere of H2 and Ar with a volume ratio of 1:9 to obtain a catalyst for hydrogen storage material.

[0081] This embodiment also provides a method for preparing a hydrogen storage material, comprising the following steps:

[0082] In a glove box filled with argon, the catalyst for hydrogen storage material, MgH2 material and stainless steel balls were transferred to a stainless steel ball mill and sealed; then 3MPa hydrogen was introduced, followed by ball milling at 500rpm for 24h to obtain 0.0952g of hydrogen storage material; based on the total mass of the hydrogen storage material, the mass fraction of the catalyst for hydrogen storage material was 10%, and the hydrogen storage material was recorded as MgH2-10wt.%0.05NiPd / CeO2.

[0083] Example 2

[0084] The difference between this embodiment and embodiment 1 is that in the catalyst for hydrogen storage material, the ratio of the total number of atoms of the Ni element and the Pd element to the number of atoms of the CeO2 nanorods is 0.1.

[0085] The remaining parameters remain the same as those in Example 1.

[0086] Example 3

[0087] The difference between this embodiment and embodiment 1 is that in the catalyst for hydrogen storage material, the ratio of the total number of atoms of the Ni element and the Pd element to the number of atoms of the CeO2 nanorods is 0.2.

[0088] The remaining parameters remain the same as those in Example 1.

[0089] Figure 1 The TEM image of the catalyst for hydrogen storage material provided in this embodiment is shown. It can be seen from the figure that nanorods are loaded with nanoclusters.

[0090] Figure 2 The SEM image of the hydrogen storage material provided in this embodiment is shown. It can be seen from the figure that the particle size of the hydrogen storage material is relatively small.

[0091] Under the condition of 0.001Mpa H2, the temperature was raised to different set temperatures (250°C, 275°C, 300°C, 325°C and 350°C) at a heating rate of 5°C / min in a programmed temperature rising manner to test the dehydrogenation performance of the hydrogen storage material provided in this embodiment at different temperatures. The test results are shown in FIG. Figure 3 As shown in the figure, it can be seen that the hydrogen storage material of the present invention can release 6.4wt.% of hydrogen within 500s at 350°C; and at 275°C, the dehydrogenation amount reaches 5.5wt.% within 2000s.

[0092] The hydrogen storage material provided in this embodiment was heated to 350°C at a heating rate of 5°C / min under the condition of 0.001Mpa H2, and the gas was evacuated and cooled to room temperature to achieve dehydrogenation after holding for 10 minutes. Then, the hydrogen absorption performance test was performed: under the condition of 5.0MPa H2, the temperature was raised to different set temperatures (100°C, 150°C, 200°C and 250°C) at a heating rate of 5°C / min in a programmed temperature rising manner, so as to test the hydrogen absorption performance of the hydrogen storage material provided in this embodiment at different temperatures. The test results are shown in FIG. Figure 4 As shown in the figure, it can be seen that the hydrogen storage material of the present invention can absorb 6.4wt.% of hydrogen within 40s at 250°C; and at 100°C, the hydrogen absorption reaches 4wt.% within 2500s.

[0093] In summary, Figure 3 and Figure 4 It can be seen that the hydrogen storage material provided in this embodiment exhibits excellent hydrogen absorption / desorption kinetics, a fast hydrogen absorption / desorption rate, and still has excellent hydrogen absorption / desorption performance at a relatively low temperature.

[0094] Example 4

[0095] The difference between this embodiment and embodiment 1 is that in the catalyst for hydrogen storage material, the ratio of the total number of atoms of the Ni element and the Pd element to the number of atoms of the CeO2 nanorods is 0.3.

[0096] The remaining parameters remain the same as those in Example 1.

[0097] Example 5

[0098] The difference between this embodiment and embodiment 3 is that in the hydrogen storage material, the mass fraction of the catalyst for the hydrogen storage material is 5% based on the total mass of the hydrogen storage material.

[0099] The remaining parameters remain the same as those in Example 3.

[0100] Example 6

[0101] The difference between this embodiment and embodiment 3 is that in the hydrogen storage material, the mass fraction of the catalyst for the hydrogen storage material is 15% based on the total mass of the hydrogen storage material.

[0102] The remaining parameters remain the same as those in Example 3.

[0103] Example 7

[0104] The difference between this embodiment and embodiment 3 is that during the preparation of the hydrogen storage material, the ball milling time is 12 hours.

[0105] The remaining parameters remain the same as those in Example 3.

[0106] Example 8

[0107] The difference between this embodiment and embodiment 3 is that the molar amount of NiCl2 in step (3) is replaced by CoCl2, and the molar amount of H2PdCl4 is replaced by KMnO4, so that the catalyst for hydrogen storage material includes CeO2 nanorods and CoMn nanoclusters loaded on CeO2 nanorods.

[0108] The remaining parameters remain the same as those in Example 3.

[0109] Comparative Example 1

[0110] The difference between this comparative example and Example 3 is that no catalyst for hydrogen storage material is added when preparing the hydrogen storage material.

[0111] The remaining parameters remain the same as those in Example 3.

[0112] Under the condition of 0.001Mpa H2, the temperature was raised to different set temperatures (250°C, 275°C, 300°C, 325°C and 350°C) at a heating rate of 5°C / min by programmed temperature rise, so as to test the dehydrogenation performance of the hydrogen storage material provided in this comparative example at different temperatures. The test results are shown in FIG. Figure 5 As shown in the figure, it can be seen that the dehydrogenation rate is slow when no catalyst is added, and the amount of hydrogen released after 2500 seconds at 275°C is only 1.1wt.%.

[0113] The hydrogen storage material provided in this comparative example was heated to 350°C at a heating rate of 5°C / min under the condition of 0.001Mpa H2, and the gas was evacuated and cooled to room temperature to achieve dehydrogenation after holding for 10 minutes. The hydrogen absorption performance was then tested: under the condition of 5.0MPa H2, the temperature was raised to different set temperatures (100°C, 150°C, 200°C and 250°C) at a heating rate of 5°C / min by a programmed temperature increase method, so as to test the hydrogen absorption performance of the hydrogen storage material provided in this comparative example at different temperatures. The test results are shown in FIG. Figure 6 As shown in the figure, it can be seen that the hydrogen absorption rate is very slow without adding a catalyst.

[0114] Comparative Example 2

[0115] The difference between this comparative example and Example 3 is that when preparing the catalyst for hydrogen storage material, NiCl2 is not added, so that the catalyst for hydrogen storage material does not contain Ni element.

[0116] The remaining parameters remain the same as those in Example 3.

[0117] Comparative Example 3

[0118] The difference between this comparative example and Example 3 is that H2PdCl4 is not added when preparing the catalyst for hydrogen storage material, so that the catalyst for hydrogen storage material does not contain Pd element.

[0119] The remaining parameters remain the same as those in Example 3.

[0120] Comparative Example 4

[0121] The difference between this comparative example and Example 3 is that when preparing the catalyst for hydrogen storage material, NiCl2 and H2PdCl4 are not added, so that the catalyst for hydrogen storage material does not contain Ni element and Pd element.

[0122] The remaining parameters remain the same as those in Example 3.

[0123] The following tests were performed on the hydrogen storage materials provided in the above examples and comparative examples:

[0124] ① Under the condition of 0.001Mpa H2, the hydrogen storage material is heated at a rate of 2°C / min. When the dehydrogenation amount reaches 0.1wt.%, the corresponding dehydrogenation temperature is recorded as the starting dehydrogenation temperature.

[0125] ② Under the condition of 0.001Mpa H2, heat to 300℃ at a rate of 5℃ / min, then dehydrogenate the hydrogen storage material at a constant temperature, and record the time taken for complete dehydrogenation.

[0126] ③ Under the condition of 0.001Mpa H2, the hydrogen storage material was heated to 350℃ at a heating rate of 5℃ / min. After holding for 10 minutes, the gas was evacuated and cooled to room temperature to achieve dehydrogenation. Then, the hydrogen absorption capacity was tested: under the condition of 5.0MPa H2, the temperature was raised to 100℃ at a rate of 5℃ / min, and the hydrogen absorption treatment was carried out at a constant temperature for 2500s, and the hydrogen absorption capacity was recorded.

[0127] ④ Under the condition of 0.001Mpa H2, the hydrogen storage material is heated at a rate of 2℃ / min, and the maximum dehydrogenation amount after complete dehydrogenation is recorded.

[0128] ⑤ Under the condition of 0.001Mpa H2, the hydrogen storage material is heated to 350℃ at a heating rate of 5℃ / min. After holding for 10min, the gas is evacuated and cooled to room temperature to achieve dehydrogenation. Then a cyclic performance test is carried out: at 300℃, the hydrogen storage material is allowed to absorb hydrogen for 30min under the condition of 5.0MPa H2 and desorb hydrogen for 15min under the condition of 0.001Mpa H2. After 20 cycles of hydrogen absorption and desorption, the ratio of the 20th hydrogen absorption amount to the 1st hydrogen absorption amount is calculated to obtain the hydrogen storage capacity retention rate.

[0129] The above test results are shown in Table 1.

[0130] Table 1

[0131]

[0132]

[0133] analyze:

[0134] It can be seen from Examples 1-6 that a catalyst for hydrogen storage material provided by the present invention includes CeO2 nanorods and trace amounts of NiPd nanoclusters loaded on CeO2 nanorods, which can greatly reduce the amount of precious metals used. By compounding the catalyst for hydrogen storage material with MgH2 material, a hydrogen storage material with low dehydrogenation temperature, fast reversible hydrogen absorption / dehydrogenation rate, high hydrogen storage capacity and good cycle performance can be obtained.

[0135] By comparing Example 3 with Example 7, it can be seen that if the ball milling time is reduced, the particle size of the hydrogen storage material will increase, the uniformity of the phase distribution will decrease, the kinetics will slow down, and the cycle performance will deteriorate.

[0136] It can be seen from Example 3 and Example 8 that Example 8 provides a catalyst for a hydrogen storage material including CeO2 nanorods and trace amounts of CoMn nanoclusters loaded on the CeO2 nanorods. By compounding the catalyst for the hydrogen storage material with the MgH2 material, it is also possible to lower the dehydrogenation temperature of the hydrogen storage material, and improve the reversible hydrogen absorption / desorption rate and cycle performance, but the effect is slightly worse than that of the catalyst loaded with NiPd element in Example 3, and the maximum dehydrogenation amount of the hydrogen storage material provided by Example 8 is lower than that of Example 3, that is, the hydrogen storage amount is lower than that of Example 3.

[0137] By comparing Example 3 with Comparative Example 1, it can be seen that if no catalyst is added, the obtained hydrogen storage material is still MgH2, and its initial dehydrogenation temperature is relatively high, higher than 300°C, and it will cause the particle size of the hydrogen storage material to increase, the hydrogen absorption / desorption kinetics to be greatly slowed down, and the cycle performance to deteriorate.

[0138] From the comparison between Example 3 and Comparative Example 2, it can be seen that if the catalyst for hydrogen storage material does not contain Ni element, the catalytic effect of the catalyst will be weakened and the kinetics of hydrogen absorption / desorption will be slowed down.

[0139] From the comparison between Example 3 and Comparative Example 3, it can be seen that if the catalyst for hydrogen storage material does not contain Pd element, the catalytic effect of the catalyst will be weakened and the kinetics of hydrogen absorption / desorption will be slowed down.

[0140] From the comparison between Example 3 and Comparative Example 4, it can be seen that if the catalyst for hydrogen storage material does not contain Ni and Pd elements, the catalytic effect of the catalyst will be greatly weakened and the kinetics of hydrogen absorption / desorption will be slowed down.

[0141] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.

Claims

1. A catalyst for hydrogen storage material, characterized in that The catalyst for hydrogen storage material includes CeO2 nanorods and transition metal nanoclusters supported on the CeO2 nanorods; The transition metal nanoclusters include any two of the elements Ni, Pd, Co or Mn.

2. The catalyst for hydrogen storage material according to claim 1, characterized in that The length of the CeO2 nanorods is 50-80nm; Preferably, the diameter of the CeO2 nanorods is 7-8 nm.

3. The catalyst for hydrogen storage material according to claim 1 or 2, characterized in that: The transition metal nanoclusters include Ni and Pd elements; Preferably, the ratio of the total number of atoms of the Ni element and the Pd element to the number of atoms of the CeO2 nanorods is 0.05-0.3; Preferably, the molar ratio of the Ni element to the Pd element is (1-3):(1-3).

4. The catalyst for hydrogen storage material according to claim 1 or 2, characterized in that The transition metal nanoclusters include Co and Mn elements; Preferably, the ratio of the total number of atoms of the Co element and the Mn element to the number of atoms of the CeO2 nanorods is 0.05-0.3; Preferably, the molar ratio of the Co element to the Mn element is (1-3):(1-3).

5. A method for preparing a catalyst for hydrogen storage material according to any one of claims 1 to 4, characterized in that: The preparation method comprises: (1) mixing CeO2 nanorods, a transition metal source and a solvent for loading to obtain a loaded product; wherein the transition metal source comprises any two of a Ni source, a Pd source, a Co source or a Mn source; (2) The supported product is subjected to a heating reduction reaction to obtain the catalyst for the hydrogen storage material.

6. The preparation method according to claim 5, characterized in that: The preparation method of CeO2 nanorods in step (1) comprises: (a) mixing a solution containing a Ce source and a solution containing a precipitant, and then performing a hydrothermal reaction to obtain a hydrothermal reaction product; (b) calcining the hydrothermal reaction product to obtain the CeO2 nanorods; Preferably, the Ce source comprises a Ce salt; Preferably, the precipitant comprises an alkaline substance; Preferably, the temperature of the hydrothermal reaction is 90-110°C, and the time of the hydrothermal reaction is 22-26h; Preferably, the calcination temperature is 380-420° C., and the calcination time is 3-5 h.

7. The preparation method according to claim 5 or 6, characterized in that: The mixing in step (1) specifically comprises the following steps: firstly performing a first mixing, then adding a pH adjusting agent dropwise until the pH value of the system is 9-10, and then performing a second mixing; Preferably, the first mixing and the second mixing are both accompanied by stirring; Preferably, the first mixing time is 20-40 min; Preferably, the second mixing time is 1-3 hours.

8. The preparation method according to any one of claims 5 to 7, characterized in that: The atmosphere of the heating reduction reaction in step (2) is a reducing atmosphere; Preferably, the gas in the reducing atmosphere includes hydrogen and argon; the volume ratio of the hydrogen to the argon is (1-2):(8-9); Preferably, the temperature of the heating reduction reaction is 380-420°C; Preferably, the heating reduction reaction time is 3-5h.

9. The preparation method according to any one of claims 5 to 8, characterized in that: The preparation method specifically comprises the following steps: (I) dissolving Ce(NO3)3·6H2O in water to obtain a solution containing a Ce source, and dissolving NaOH in water to obtain a solution containing a precipitant; rapidly mixing the solution containing a Ce source and the solution containing a precipitant under stirring, and continuing to stir and mix at room temperature for 1-2 hours, and then performing a hydrothermal reaction at 90-110°C for 22-26 hours, and then washing and vacuum drying in sequence to obtain a hydrothermal reaction product; calcining the hydrothermal reaction product at 380-420°C for 3-5 hours to obtain CeO2 nanorods; (II) dispersing the CeO2 nanorods, NiCl2 and H2PtCl4 in water, stirring and mixing at room temperature for 20-40 minutes, then adding a pH adjuster dropwise until the pH value of the system is 9-10, and then continuing to stir and mix for 1-3 hours to load, and then washing and vacuum drying in sequence to obtain a loaded product; (III) In a reducing atmosphere of hydrogen and argon, the supported product is subjected to a heating reduction reaction at 380-420° C. for 3-5 hours to obtain the catalyst for hydrogen storage material.

10. A hydrogen storage material, characterized in that: The hydrogen storage material is obtained by ball milling the MgH2 material and the hydrogen storage material according to any one of claims 1 to 3 with a catalyst; Preferably, based on the total mass of the hydrogen storage material, the mass fraction of the catalyst for the hydrogen storage material is 5-15%; Preferably, the rotation speed of the ball mill is 450-500 rpm; and the time of the ball mill is 20-25 h.

Citation Information

Patent Citations

  • Preparation method and application of loaded type bimetallic nano-material

    CN108161026A

  • Monoatomic noble metal / transition metal oxide composite material as well as preparation method and application thereof

    CN112044434A

  • Rhodium-based heterogeneous catalyst for propylene hydroformylation reaction as well as preparation method and application of rhodium-based heterogeneous catalyst

    CN116920836A

  • Catalyst for enhancing performance of composite hydrogen storage material as well as preparation method and application of catalyst

    CN117899884A

  • Columnar ceria catalyst

    JP2012223667A

Cited By

  • Rare earth oxide catalyst as well as preparation method and application thereof

    CN120771910A